Menyusun Strategi Marketing UMKM Di Dusun Jetis Gayu Desa Wringin Putih Kecamatan Borobudur Kabupaten Magelang - Akhmad Haq; Azahra Amalia Sugiyarto Azahra; Nabila Arkania Oktaviani Arkania (Jurnalika : Jurnal Ilmu Komunikasi, 2023)
This Integrated C ommunity Service Program was carried out in Jetis Gayu Hamlet, Wringinputih Village, Borobudur District. The majority of the people here are traders or UMKM owner. The main problem faced by UMKM in this hamlet is that the product marketing has not been optimal. Most still rely on the traditional buying and selling process. After obtaining data through field observations, there are various facts related to the obstacles experienced by UMKM in Jetis Gayu Hamlet. Therefore, an UMKM outreach program was carried out, to educate and directly practice knowledge related to marketing strategies to UMKM. In addition, this socialization was carried out door-to-door, bearing in mind that the constraints experienced by each UMKM are different. By socializing the marketing strategy, it will have impact on increasing sales from UMKM in Jetis Gayu Hamlet. Keywords: devotion, UMKM, strategy, marketing